Catalogue of the Western Asiatic seals in the British Museum: Stamp seals III: impressions of stamp seals on cuneiform tablets, clay bullae, and jar handles - Mitchell, Terence C.; Searight, Ann (Brill, 2010)
Provides an inventory of the impressions of Near Eastern stamp seals on cuneiform tablets and clay bullae, as well as on jar handles from Palestine, in the collections of the British Museum. This volume is supplemented with an Index of Subjects based on the descriptions in the Catalogue